Human Population Density is a Poor Predictor of Debris in the Environment - Schuyler, Qamar; Wilcox, Chris; Lawson, T. J.; Ranatunga, R. R. M. K. P.; Hu, Chieh-Shen; Global Plastics Project Partners; Hardesty, Britta Denise (Frontiers in Environmental Science, 2021)
There have been a variety of attempts to model and quantify the amount of land-based waste entering the world’s oceans, most of which rely heavily on global estimates of population density as the key driving factor. Using empirical data collected in seven different countries/territories (China, Kenya, South Africa, South Korea, Sri Lanka, Taiwan and Vietnam), we assessed a variety of different factors that may drive plastic leakage to the environment. These factors included both globally available GIS data as well as observations made at a site level. While the driving factors that appear in the best models varied from country to country, it is clear from our analyses that population density is not the best predictor of plastic leakage to the environment. Factors such as land use, infrastructure and socio-economics, as well as local site-level variables (e.g., visible humans, vegetation height, site type) were more strongly correlated with plastic in the environment than was population density. This work highlights the importance of gathering empirical data and establishing regular monitoring programs not only to form accurate estimates of land-based waste entering the ocean, but also to be able to evaluate the effectiveness of land-based interventions.